Chamaerops humilis L. FRUIT PULP VALORIZATION: A DESIGN OF EXPERIMENTS APPROACH TO POWDER PRODUCTION AND PHYSICOCHEMICAL CHARACTERIZATION - Hamza Derraji; Badreddine El Mejhed; Fouzia Kzaiber; Wafa Terouzi (Mesopotamia Journal of Agriculture, 2024)
In response to demographic pressures and environmental imperatives, this study focuses on the valorization of Chamaerops humilis L. fruit in the Beni Mellal Khenifra region. The native palm, known as "Doum," holds nutritional and medicinal significance, prompting a detailed exploration. Extracts from its leaves and fruits have been historically used in traditional medicine, showcasing anti-oxidant properties and therapeutic effects on various ailments. This study seeks to optimize Chamaerops humilis L. fruit pulp powder production using the design of experiments (DOE) and physicochemical characterization. A full factorial design approach is applied to systematically optimize the process, focusing on key variables like Temperature and Time. Physicochemical analysis reveals essential details concerning pH (4.205), titratable acidity (1.47), moisture content (10.85%), and ash content (2.9325%). The study identifies optimal conditions, such as temperature = 65°C and time = 6 hours, for maximum yield and desirable properties. Additionally, water absorption (WAI) and solubility indices (WSI) are investigated, revealing the influence of drying and different agitation temperatures. The Pareto diagram underscores the significant impact of these factors, contributing to our understanding of the quality parameters of Chamaerops humilis L. powder. The results offer valuable insights for sustainable practices in utilizing this botanical resource.